A smart home foundation scheme based on open source hardware and cloud computing. (2017) - Zhou, Wei; Xu, Jian; Wang, Bin
In recent years, many internet of things (IoT) platforms based on cloud computing have been proposed for general purpose applications. Though many similar platforms or schemes particular for smart home applications have been proposed, many issues such as multiple connectivity due to diversity of smart home applications and supporting for real-time operations have not been solved properly. We propose a smart home foundation scheme adopting open source hardware devices and cloud computing technology to explore these issues. In this scheme, Arduino Yun-based smart hardware devices can connect to the cloud server through multiple network connectivity. By utilising Spacebrew technology, a bidirectional real-time communication can be implemented which provides a solid foundation for real-time operations of smart home. The core functions of the scheme are exposed through RESTful web services in a SaaS (short for software as a service) manner and can be called by various clients and other applications. Demonstrative applications show that the proposed smart home foundation scheme provides adequate support for creating smart home applications based on wireless open source hardware devices.